Application of the Methods of Monitoring and Detecting the Belt Mistracking in Laboratory Conditions - Przemysław Dąbek; Adam Wróblewski; Jacek Wodecki; Piotr Bortnowski; Maksymilian Ozdoba; Robert Król; Radosław Zimroz (Applied Sciences, 2023)
Belt mistracking is one of the most dangerous and costly failures of belt conveyors. This phenomenon can lead to complete damage to the conveyor belt, increased demand for electricity from the drive, accelerated wear of route elements, and poses a fire hazard. The article presents the most important causes and ways to detect belt mistracking. Based on the tests carried out at the laboratory test rig, the mechanical and operating parameters of the electric drive of conveyor operation burdened with the problem of lateral running off for the tested belt were compared. The mistracking causes a sudden, differentiated increase in the resistance to movement of the machine, which directly affects the recorded values of forces in the drive system and tensioning mechanism and increases the electrical energy consumption of the drive motor. Belt run monioring based on these parameters is not precise, because there are many other factors on the conveyor route, potentially responsible for the increase in recorded currents and forces. The paper presents an analysis of the possibility of using three, non-contact methods directly monitoring the lateral run-off of the belt, based on vibration measurements of conveyor pulley bearing, RGB images, thermal imaging and measuring the compressive force on the tensioning device.